2011
DOI: 10.1016/j.rmed.2010.12.020
|View full text |Cite
|
Sign up to set email alerts
|

COPD severity score as a predictor of failure in exacerbations of COPD. The ESFERA study

Abstract: Clinical failure after ambulatory treatment of exacerbation of COPD is frequent. Usual markers of severity (impaired lung function, active smoking and severe dyspnoea) are associated with failure; however, a short severity questionnaire (COPDSS) provides better predictive value than the usual variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 36 publications
3
37
0
1
Order By: Relevance
“…The COPDSS was adopted into routine clinical practice after previous validation studies [26,27]. Unlike the BODE index [31], the other indices do not require the performance of exercise testing and could be calculated from the data recorded during the routine health care process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The COPDSS was adopted into routine clinical practice after previous validation studies [26,27]. Unlike the BODE index [31], the other indices do not require the performance of exercise testing and could be calculated from the data recorded during the routine health care process.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that these indices may be useful in the assessment of COPD severity as well as in the prediction of different negative events in ambulatory COPD patients (e.g. mortality, health care utilisation, future hospitalisations, failures in COPD exacerbations) [24,25,26,27,28,29,30], but to our knowledge, no studies have investigated their usefulness in hospitalised patients. We found that the COPDSS, BODEx and DOSE but not the ADO index were associated with adverse outcome on univariate analysis, but only the BODEx and DOSE indices appeared as independent adverse prognostic factors in the multivariate models B and C, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also calculated modifications of the BODE index, including the mBODE (which replaces 6MWD with oxygen uptake) [20], e-BODE (BODE plus exacerbations) [21], and BODEx (substitution of exacerbations for exercise capacity) [21]. We also calculated the ADO index (age, dyspnoea and FEV1) [22], the COPD Prognostic Index (CPI) (quality of life standardised by the Chronic Respiratory Questionnaire (CRQ) or St George's Respiratory Questionnaire (SGRQ), FEV1, age, sex, BMI, exacerbation history and cardiovascular disease history) [23], the SAFE index (quality of life by SGRQ, FEV1 and 6MWD) [24], the HADO index (health status, activity, dyspnoea and FEV1) [25], the COPDSS-COPD severity score (respiratory symptoms, systemic corticosteroid use, other COPD medication use, previous hospitalisation or intubation for respiratory disease and home oxygen use) [26,27], TARDIS (age, BMI, dyspnoea, airflow obstruction, hospitalisations and influenza vaccination) [28], and the DOSE index (dyspnoea, smoking status, FEV1 and prior exacerbation history) [29]. Comorbidities were quantified by means of the Charlson index, excluding COPD [30].…”
Section: Indices Calculationsmentioning
confidence: 99%
“…Near to these results, Miravitlles et al, 2011 (11) found more frequent exacerbation in patients in need for invasive MV (2.6±1.7) than those not requiring it (2.5±2) but to an insignificant degree. This may be explained that they studied frequency of exacerbations in the last year only.…”
Section: Jmscr Vol||06||issue||06||page 1024-1032||june 2018mentioning
confidence: 90%